Meta‐analysis of mindfulness training on teacher well‐being - Zarate, Kary; Maggin, Daniel M.; Passmore, Amanda (Psychology in the schools, 2019)
Teachers are reporting increased incidence of stress, depression, burnout, and anxiety resulting in overall poor mental health and well‐being outcomes. Recently, mindfulness‐based interventions have emerged as having the potential to improve these deleterious impacts. This meta‐analysis investigated the effects of mindfulness‐based interventions on educators in schools. To be included in the review, studies must have been printed in English, used a methodology that included a control group with in‐service teachers as the primary participants. In addition, the intervention needed to have mindfulness as a major component. The search procedures led to the identification of 18 manuscripts that included a total sample of 1,001 educators. Mindfulness interventions ranged greatly in dosage, frequency, and delivery model. Using a random effects model, mindfulness‐based interventions were found to have significant positive effects across all domains. Mindfulness‐based interventions resulted in large effects on feelings of mindfulness, moderate effects for decreases in stress and anxiety, and small effects on feelings of depression and burnout. Discussion includes the quality of the literature base as well as implications for future research.